Zur Problematik der Abgrenzung von Kunstlandschaften: dargestellt am Beispiel der Po-Ebene - Lehmann, Herbert (ERDKUNDE, 1961)
The paper takes as its starting point the comprehensive denifition of region of fine art as put forward in the new book by the Frankfurt art historian, Harald Keller. According to him the character of an art region can only be deduced from a basically similar behaviour in all style periods. Using the Po plain as an example, this paper shows that this principle leads to methodological difficulties as soon as the boundaries of art regions are to be cartographically presented or if areas with only a single creative climax in the development of art are to be classified art-geographically. A provisional classification of the Po plain into partly overlapping art zones based on an historical map (fig. 1) attempts to overcome this difficulty. A different art-geographical classification based on building material is discussed on the basis of the work le pictre delle città d’Italia by Francesco Rodolico, and a map of the sources of building materials of artistic monuments of the Po plain (fig. 3).